Clinical study of peanut and nut allergy in 62 consecutive patients: new features and associations. - Ewan, P. W. (BMJ Group, 1996)
OBJECTIVE--To investigate clinical features of acute allergic reactions to peanuts and other nuts. DESIGN--Analysis of data from consecutive patients seen by one doctor over one year in an allergy clinic at a regional referral centre. SUBJECTS--62 patients aged 11 months to 53 years seen between October 1993 and September 1994. MAIN OUTCOME MEASURES--Type and severity of allergic reactions, age at onset of symptoms, type of nut causing allergy, results of skin prick tests, and incidence of other allergic diseases and associated allergies. RESULTS--Peanuts were the commonest cause of allergy (47) followed by Brazil nut (18), almond (14), and hazelnut (13). Onset of allergic symptoms occurred by the age of 2 years in 33/60 and by the age of 7 in 55/60. Peanuts accounted for all allergies in children sensitised in the first year of life and for 82% (27/33) of allergies in children sensitised by the third year of life. Multiple allergies appeared progressively with age. The commonest symptom was facial angioedema, and the major feature accounting for life threatening reactions was laryngeal oedema. Hypotension was uncommon. Of 55 patients, 53 were atopic--that is, had positive skin results of tests to common inhaled allergens--and all 53 had other allergic disorders (asthma, rhinitis, eczema) due to several inhaled allergens and other foods. CONCLUSIONS--Sensitisation, mainly to peanuts, is occurring in very young children, and multiple peanut/nut allergies appear progressively. Peanut and nut allergy is becoming common and can cause life threatening reactions. The main danger is laryngeal oedema. Young atopic children should avoid peanuts and nuts to prevent the development of this allergy.